PENGARUH PROMOSI DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SEPEDA MOTOR PADA PD UTAMA MOTOR LUBUKLINGGAU - Yusup Yusup; Ronal Aprianto (LPPM UNIVERSITAS BINA INSAN, 2016)
The sample of this study was 90 respondents who were consumers of PD Utama Motor Lubuklinggau. Based on the results of the study, the regression equation is Y = 19,296 + 0,282 X1 + 0,405 X2. The meaning of the equation is that the value of constant is 19,296, this means that if there is no promotion and service variable then the decision is 21,986, while the promotion coefficient value (b1) is 0.282 means that every increase in one variable promotion unit will increase the purchasing decision by 0.282 units. Then the service regression coefficient value of b2 = 0.405 means that every increase in one service unit variable will increase the purchase decision by 0.405. From the calculation of the Model Summary, it can be seen that the value of R2 (R Square) or determination is 0.536, the contribution of promotion and service variables on consumer purchasing decisions of Lubuklinggau PD Utama Motorbike motorcycles is 53.6%, while the remaining 45.4% is influenced by other factors.